Setting up and running a small meat or fish processing enterprise - Axtell, Barrie; Fellows, Peter (Technical Centre for Agricultural and Rural Cooperation, 2004)
This second publication in the CTA series of food processing manuals, compiled by contributors from several developing countries, covers markets and marketing for meat and fish, planning production, meat processing, fish processing, quality assurance and legislation, and financial management (See also 1041, 1176).